2020
DOI: 10.35794/jmbi.v7i3.30668
|View full text |Cite
|
Sign up to set email alerts
|

Reaksi Pasar Modal Terhadap Peristiwa Virus Corona (Covid-19) Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia

Abstract: The capital market is not only a funding facility for the companies but also means for investment activities. So many roles of the capital market in economic activities will have an impact on the sensitivity of the market reaction to events that occur. At the end of 2019, a new virus emerged in China, called the Corona Virus Disease 2019 or COVID-19. In Indonesia, the first case of COVID-19 was approved directly by President Joko Widodo on March 2020. The purpose of this research is to discover informations re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 1 publication
(1 reference statement)
2
6
0
15
Order By: Relevance
“…It can be said that the announcement of the PSBB policy in DKI Jakarta is an event that has a large enough effect. The results of this study support the research conducted by Sambuari et al (2020), which proves that there is an influence during the Covid-19 virus event, which is indicated by a significant trading volume activity.…”
Section: Discussionsupporting
confidence: 89%
“…It can be said that the announcement of the PSBB policy in DKI Jakarta is an event that has a large enough effect. The results of this study support the research conducted by Sambuari et al (2020), which proves that there is an influence during the Covid-19 virus event, which is indicated by a significant trading volume activity.…”
Section: Discussionsupporting
confidence: 89%
“…Previous research conducted by (Sambuari et al, 2020) found that this event did not contain information that caused the market to not react. This event did not contain information, so there was no reaction and did not have a major impact on market activities in the capital market, particularly in the food and beverage sub-sector.…”
Section: Introductionmentioning
confidence: 86%
“…[10] research results show that there are significant differences in stock trading volumes before and during Covid-19 in manufacturing companies in the consumer goods industry sector, as well as the results of [7] research on hotel, restaurant, and tourism companies. [11] also stated the results of the same study that the announcement of the first case of the Corona Virus in food and beverage companies contained information that caused the capital market to react to the frequency of trading in terms of trading transaction activities.This research is motivated by previous research studies which showed the same results for different objects. The researcher sees that the total shares traded are the most important factor in the sustainability of the company's business as well as an indicator in determining the performance of a company so that this research is deemed necessary to be carried out.…”
Section: Introductionmentioning
confidence: 94%